In‐patient discharge rates for the irritable bowel syndrome – an analysis of national trends in the United States from 1997 to 2010. Issue 11 (29th October 2013) - Sethi, S.; Wadhwa, V.; LeClair, J.; Mikami, S.; Park, R.; Jones, M.; Sethi, N.; Brown, A.; Lembo, A.
Summary: Background: Irritable bowel syndrome (IBS) is one of the most common out‐patient diagnoses in primary care and gastroenterology. There are limited data on the rate and costs associated with in‐patient discharges for IBS. Aim: To estimate the incidence and costs of hospital discharges for IBS in the United States. Methods: We analysed the National Inpatient Sample database for all subjects in which IBS (ICD‐9 code: 564.1) was the principal discharge diagnosis from 1997 to 2010. The National Inpatient Sample contains data from approximately 8 million hospital stays each year. Our findings reflected patient and hospital characteristics like geographical region and bed size. Results: In 1997, there were 11 433 patients with a principal discharge diagnosis of IBS as compared to 12 842 in 2010 ( P > 0.9, GoF test). The mean length of stay for IBS also remained the same between 1997 and 2010 at 3.7 ± 0.1 days. However, during this period, the mean hospital charges per hospitalization increased by 207.8% from 6873 ± 198 in 1997 to 21 153 ± 598 in 2010 ( P < 0.01). The aggregate charges (i.e., 'national bill') for IBS increased by 245.5% from 78 524 129 ± 3 781 316 in 1997 to 271 311 405 ± 14 023 289 in 2010 ( P < 0.01). Conclusions: The number of in‐patient discharges and length of stay for IBS have remained relatively stable between 1997 and 2010, whereas the cost associated with these discharges has increased significantly. In‐patient costs associated with IBS contribute significantly to the total healthcare bill. Further research on the cost‐effectiveness of diagnostic procedures and therapies in IBS is required.